PENCIPTAAN MEDIA PROMOSI WISATA GUNUNG BROMO BERBASIS WEBSITE UNTUK MENINGKATKAN LOYALITAS PENGUNJUNG - Sugianto, Febrian; Fianto, Achmad Yanu Alif; Sutikno, Sutikno (Jurnal Art Nouveau, 2015)
Abstract: Â Mount Bromo (from Sanskrit) volcano is still active and most famous as a tourist attraction in East Java. As a tourist attraction, Mount Bromo become attractive because of its status as the volcano is still active.The objective of this media campaign, so Places Mount Bromo in Probolinggo be better known by the public outside of Probolinggo and to increase visitor loyalty Mount Bromo for visitors interested in returning to Mount Bromo. Making the media campaign is based on the collection of data and surveys directly in Places of Mount Bromo. Results from making media campaign is expected to introduce Places Mount Bromo to the public. And is expected to also be applied to digital media.Â Keywords: Mount Bromo, Promotion, Ecotourism, Website.